Systematic Review of Learning Generic Skills in Higher Education—Enhancing and Impeding Factors - Tuononen, Tarja; Hyytinen, Heidi; Kleemola, Katri; Hailikari, Telle; Männikkö, Iina; Toom, Auli (Frontiers in Education, 2022)
The research field on generic skills in higher education has expanded rapidly. In addition, the importance of generic skills has been highlighted both in educational policy discourses and in practice of higher education. The present study reviews theoretical, methodological, and empirical viewpoints on learning generic skills and synthesizes the empirical evidence about the factors that enhance and impede student learning of generic skills. Altogether 116 articles were included in the analysis. The systematic analysis revealed remarkable variation in concepts, research methods, and operationalization of generic skills. These findings suggest that research in this field is still incoherent. According to the results, contextual factors that enhance or impede higher education students’ learning of generic skills were investigated more often than individual factors. Furthermore, the articles included in this review emphasized learning of work-oriented professional skills over higher-order thinking skills. To ensure the development of research on generic skills, it is important to focus on more coherent theorization and operationalization of the various generic skills. More longitudinal studies with methods that genuinely capture actual skills and their development are also needed to advance the field. The results can be used for future discussions on theorization, empirical research, and practical development of student learning of generic skills.